2011
DOI: 10.1080/08897077.2011.599255
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Utility of Brief Alcohol Use Disorders Identification Test (AUDIT) for Human Immunodeficiency Virus Antiretroviral Medication Nonadherence

Abstract: Alcohol use negatively affects adherence to antiretroviral therapy (ART), thus HIV/AIDS providers need accurate, efficient assessments of alcohol use. Using existing data from an efficacy trial of two cognitive-behavioral ART adherence interventions, we sought to determine if results on two common alcohol screening tests (Alcohol Use Disorders Identification Test—Consumption (AUDIT-C) and its binge-related question (AUDIT-3)) predict ART nonadherence. Twenty seven percent of the sample (n=308) were positive on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 34 publications
1
18
0
1
Order By: Relevance
“…In the present study, ART adherence was not associated with alcohol use or severity. However, multiple previous studies have identified associations between alcohol use and non-adherence to ART (5, 8, 10, 36). Because ART prescription and suboptimal adherence were study eligibility criteria, the present findings may not be generalizable to other samples of older PLWH, especially those with more variable adherence to ART.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the present study, ART adherence was not associated with alcohol use or severity. However, multiple previous studies have identified associations between alcohol use and non-adherence to ART (5, 8, 10, 36). Because ART prescription and suboptimal adherence were study eligibility criteria, the present findings may not be generalizable to other samples of older PLWH, especially those with more variable adherence to ART.…”
Section: Discussionmentioning
confidence: 99%
“…Using a large variety of measures and definitions of unhealthy alcohol use, these studies have reported prevalences ranging from 8% on the low end (1) to approximately 42% on the high end (12, 14). Studies specifically using the AUDIT-C have identified prevalences ranging from 14% – 27% (8, 11, 13, 15, 33). The prevalence of unhealthy alcohol use identified using the AUDIT-C in the present study—22%—falls well within the range of previous estimates among PLWH and is similar to the general prevalence in the U.S. population (22.6%) (29).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finding from previous studies report contradictory outcomes, with the majority reporting a relationship between alcohol and adherence, with higher alcohol use being associated with lower adherence (Harris et al, 2011;Teixeira et al, 2013;Raboud et al, 2011;Broyles et al, 2011). In this study, it is possible that a relationship was not found between alcohol use and adherence because data were assessed at baseline and end of the intervention, it is possible that more changes could have been observed at 3, 6 months and 12 months post-intervention.…”
Section: Hypothesis 3bmentioning
confidence: 68%